2020
DOI: 10.3382/ps/pez533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Achyranthes japonica extract supplementation on the growth performance, total tract digestibility, cecal microflora, excreta noxious gas emission, and meat quality of broiler chickens

Abstract: The present study was investigated the effects of dietary Achyranthes japonica extract ( AJE ) supplementation on the growth performance, total tract digestibility, cecal microflora, excreta noxious gas emission, breast meat quality, and organ weight in broiler chickens. In total, 640 Ross × Ross male broiler chickens (1-day-old) were randomly distributed into 4 dietary treatments with 10 replicate cages (16 birds/replicate) per treatment group for 5 wk. The dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 39 publications
12
62
0
Order By: Relevance
“…In the current study, ABP decreased the relative weight of abdominal fat but increased breast meat, which was in agreement with our recent study in broilers ( Park and Kim, 2020 ). The reason for the decreased relative weight of abdominal fat may be because of the lipolytic effect of ABP ( Krishnakumari and Priya, 2006 ; Latha et al., 2011 ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In the current study, ABP decreased the relative weight of abdominal fat but increased breast meat, which was in agreement with our recent study in broilers ( Park and Kim, 2020 ). The reason for the decreased relative weight of abdominal fat may be because of the lipolytic effect of ABP ( Krishnakumari and Priya, 2006 ; Latha et al., 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…The findings of present study showed that 0.02 to 0.04% ABP improved BWG and feed efficiency in the grower period and the whole experiment, which was consistent with the results of our recent study ( Park and Kim, 2020 ). The supplementation of ABP (0.025–0.1%) increased BWG during day 1 to 7, day 22 to 25, and day 1 to 35 as well as feed efficiency during day 1 to 7, day 8 to 21, and day 1 to 35 linearly in broilers ( Park and Kim, 2020 ). The improvement in BWG and F/G may be because of the increased nutrient digestibility.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations